Green Economy Community-Led Transformation: Economic Potential via Palm Frond Waste Artisanship in The Halal-Tourism of Eastern Aceh Ecosystem - Kurlillah, Anis; Nurjanah, Nurjanah; Munadiati, Munadiati; Hamid, Abdul; Afna, Mauloeddin (STAI Auliaurrasyidin Tembilahan, 2024)
Palm oil plantations in Eastern Aceh face a challenge: an excess of underutilized palm frond waste, creating environmental and economic burdens. To address this, a study explored empowering local communities to transform this waste into valuable handicrafts, promoting a green economic model. Despite the economic benefits of the palm oil industry, high unemployment persists, especially among the youth in palm-producing areas, with little awareness of the potential in palm frond waste. An apprenticeship program was implemented, providing hands-on training in crafting products like plates, handbags, and prayer mats. This training likely increased participants' confidence and curiosity. By equipping participants with skills before explaining the program’s aim of waste-to-wealth transformation, a strong foundation was laid. The study highlighted participants' enthusiasm and success in producing handicrafts post-training. This community-led approach, focused initially on skill development, shows potential for green economic transformation in Eastern Aceh, reducing waste and creating new income streams, potentially aligning with the region's Halal-tourism sector.